In Township Tonight: South Africa's Black City Music and Theatre, David B. Coplan, University Of Chicago Press; 2nd edition. 2008, 455 pages, Paperback: ISBN-10: 0226115674, ISBN-13: 978-0226115672. - Holtzman, Glen (International Library of African Music, 2008)
pages: 118-119
Keywords: South Africa; African Music